2014
DOI: 10.5115/acb.2014.47.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of antioxidant enzymes against transient global cerebral ischemia in gerbils

Abstract: Experimentally transient global cerebral ischemia using animal models have been thoroughly studied and numerous reports suggest the involvement of oxidative stress in the pathogenesis of neuronal death in ischemic lesions. In animal models, during the reperfusion period after ischemia, increased oxygen supply results in the overproduction of reactive oxygen species (ROS), which are involved in the process of cell death. ROS, such as superoxide anions, hydroxyl free radicals, hydrogen peroxide and nitric oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 96 publications
0
48
0
2
Order By: Relevance
“…All mice were kept under a 12-h light/dark cycle at an ambient temperature of 21±2°C and a humidity level of 60±5%. A total of 40 animals were randomly divided into four groups (n = 10): (1) control (sham-operated), (2) global cerebral IR, (3) MYR, and (4) MYR+IR. This experimental design was described in our previous study 15 .…”
Section: Methodsmentioning
confidence: 99%
“…All mice were kept under a 12-h light/dark cycle at an ambient temperature of 21±2°C and a humidity level of 60±5%. A total of 40 animals were randomly divided into four groups (n = 10): (1) control (sham-operated), (2) global cerebral IR, (3) MYR, and (4) MYR+IR. This experimental design was described in our previous study 15 .…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant capacity of brain tissue is very fragile, which makes it difficult to resist the attack of free radicals[9]. Moreover, a large number of ROS mediate tissue damage directly, which results in impaired nerve function[10,11,12,13]. Therefore, ROS are believed to be a key cause of the nerve injury after CI/R.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroprotectants commonly used in clinical treatment include calcium channel blockers, glutamate receptor antagonists and N-methyl-D-aspartic acid receptor (NMDA) antagonists. Research has shown that oxidative stress plays an important role in the pathophysiology of cerebral ischemia and that excessive ROS is produced during cerebral ischemia and reperfusion [1] . Studies have also suggested that oxidative stress and damage caused by free radicals lead are key factors for triggering stroke and other neurodegenerative diseases.…”
Section: Free Radicals and Ischemic Strokementioning
confidence: 99%
“…reperfusion [1] . Studies have also suggested that oxidative stress and damage caused by free radicals lead are key factors for triggering stroke and other neurodegenerative diseases.…”
Section: International Journal Of Neurology Researchmentioning
confidence: 99%
See 1 more Smart Citation